Upaya Meningkatkan Nilai-Nilai Moderasi Beragama Di STAI Muhammadiyah Blora Melalui Penguatan Pemahaman Kaidah Kaidah Ushul Fiqih - Nurhartanto, Armin (JURNAL PEDAGOGY, 2022)
Shari'ah according to the linguistic meaning is something that is commonly heard in life, and we are used to using it in the learning process at school, especially when delivering worship or shari'a materials. Then what exactly is the semantic meaning or linguistic meaning. Manna' Al Qathan in his book al-Tasyri' wa al fiqh fi al islam, mentions that shari'ah means all the provisions of allah that are shari'a for his servant's servant, both regarding aqidah, worship, mu'amalah and akhlaq (Qathan, t.th,:15). Thus according to him shari'a is the same as religion which includes aspects of worship, aqidah, mu'amalah and also akhlaq. His view is almost in line with Faruq Nabhan who states that shari'a is everything that Allah preaches to his servant servant (Nabhan 1981: 10). But he further stated that, istlah is often referred to for the meaning of fiqh (Nabhan, 1981: 13).Thus, Faruq Nabhan is already of the view that is... Faruq Nabhan who states that shari'a is everything that Allah preaches to his servant servant (Nabhan 1981: 10). But he further stated that, istlah is often referred to for the meaning of fiqh (Nabhan, 1981: 13). Thus, Faruq Nabhan has taken the view that the term shari'ah can be used for the meaning of fiqh, because many of the scholars use this term for this meaningthe most appropriate definition of the term shari'ah is that of Mahmud Syalthout, in his book al islam aqidah wa as sharia, namely "the provisions stipulated by Allah or the result of human understanding of the provisions of these provisions, to be used as a handle by a good human being in relationwith allah, the rest of humanity, muslims and non muslims, with the universe, and who govern this arrangement of life the scholars' divide sharia into two parts, namely the divine shari'ah and the shari'ah wadh'i Shari'ah ilahy is the provision of the law established by allah and his rosul and is now contained in the Quran and the Quran. Meanwhile, what is associated with wadh'i sharia is the legal provisions put forward by the scholars' mujtahid (Nabhan, 1981, : 11). Viewed from a linguistic point of view the word fiqih means to know something and understand it well (Faris, 1970,: III; 442) while according to the term imu islamic law fiqih means knowing the law of shari'a which is amaliah which is reviewed from one by one (Abu Zahrah, 1958:6) Viewed in terms of linguistics the word islamic law means to assign something to another, such as assigning haram to khamer, halal on milk,obligatory on five-time prayer, sunnah on the giving of se;ain zakat treasures. Medium...) The results of this study show that the importance of learning ushulfiqih in instilling a moderate attitude to all STAI Muhammadiyah Blora students, especially on the spec of shari'ah.Keywords : ushul fiqih, function, islamic law moderation